Speech Events in the Indonesian Version of Miracle in Cell No. 7 and YouTube Discussion Pages: A Digital Communication Context Analysis Using Dell Hymes’ “Speaking” Model - Nisa, Lia Khairun; Tadjuddin, Shafruddin; Ekowati, Sri Harini (Tamaddun Life, 2025)
This study investigates the structure and characteristics of speech events in two distinct communicative contexts using Dell Hymes’ SPEAKING model: the Indonesian adaptation of the film Miracle in Cell No. 7 and an online legal discussion hosted on Sahabat ICW’s YouTube channel. The research applies qualitative content analysis to identify and compare the elements of Setting, Participants, Ends, Act Sequence, Key, Instrumentalities, Norms, and Genre across both sources. In total, the film provided 129 communication segments with complex emotional and narrative elements, whereas the YouTube discussion reflected a more structured and formal discourse with 11 primary communication goals and four active participants. Findings indicate that while both contexts employ the same communicative components, their application varies significantly based on purpose, medium, and audience. The film emphasizes emotional expression and moral storytelling, illustrating themes of injustice, empathy, and human dignity through a diverse range of speech acts and multimodal cues. In contrast, the online discussion focuses on civic education and legal advocacy, employing a formal tone and structured interaction within a virtual public sphere. The study concludes that Dell Hymes’ SPEAKING model remains a robust framework for analyzing discourse in both fictional and real-time digital settings, offering critical insights into the cultural, emotional, and social dimensions of communication.